Wrongful Conviction in Texas: ‘Sex Assaults’, False Guilty Pleas, Stranger Rape with Misidentification, and Drug Offenses - Johnson, Matthew Barry; Acevedo, Janquel D. (The Wrongful Conviction Law Review)

(untitled) (University of Alberta Library, 2024)
Citing IP data, Johnson (2021), reported that sexual assault/rape was the most common offense associated with exoneration in the US. Also, stranger rape accounted for 72% of the entire IP database. To further examine the role of sexual assault, the current study examined all exonerations in Texas, the US state with the most sexual assault exonerations. Using NRE data, descriptive analyses, and reclassifying sexual assaults, we find drug offenses are the most common crime type associated with exonerations in Texas but sexual assault/rape accounts for a significant portion of Texas exonerations. Contrary to a common assumption, we also find that exculpatory DNA does not explain the substantial proportion of sexual assaults among exonerations. We also examine the role of stranger rape misidentification, youthful complainant recantations (perjury/false allegations) and false guilty pleas in the NRE Texas database. Finally, we discuss other patterns within the Texas exonerations and policy implications.